PROMOTING ETHICAL BEHAVIOUR IN NIGERIA'S PUBLIC SECTOR: THE ROLE OF QUALITY OF WORK LIFE, WORK MOTIVATION, AND JOB SATISFACTION - Ogbuabor, D. C; Okoronkwo, I. L (International Journal of Management and Allied Research (IJMAR), 2023)
This study examines the relationship between quality of work life, work motivation, job satisfaction, and ethical behavior in the Nigerian public sector. Specifically, the study explores the extent to which job satisfaction mediates the relationship between quality of work life and work motivation with ethical behavior. Data was collected from 191 mid-level employees in the Delta State Ministry of Health in Nigeria and analyzed using PLS-SEM analysis. Results suggest that job satisfaction plays a crucial role in the relationship between quality of work life and work motivation with ethical behavior. The study also found a positive correlation between job satisfaction and ethical behavior. The study offers new insights into the psychological factors that influence ethical behavior and recommends that organizations prioritize quality of work life, work motivation, and job satisfaction to foster desirable work behaviors and outcomes. This study contributes to the literature by integrating quality of work life, work motivation, job satisfaction, and ethical behavior within a single research framework in the Nigerian public sector